Asuhan Keperawatan Medikal Bedah Pada Ny. N Dengan Hipertensi Di Ruangan Rawat Inap Interne RSUD Padang Pariaman Tahun 2026 - Diva Kurnia Agustin; Hilma Yessi; Mike Asmaria; Debby Silvia Dewi (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Hypertension is a condition in which blood pressure is above the normal range. According ti data from the World Health Organization (WHO), hypertension affects 22% of the world’s population in southeast asia with an incidence rate reaching 36%. The number of hypertension sufferers in indonesia reached 34.1%, up from 25.8% in 2020. In west Sumatera province, hypertension ranks fifth out of the ten most common diseases with 63,309,620 cases. The 2024 west Sumatera provincial health office report, padang city ranked first with 23,737 cases, followed by solok in second place with 20,345 cases, and pasaman in third place with 19,907 cases. At padang pariaman regional general hospital, hypertension cases ranked sixth with 506 cases. This case study aims to apply direct nursing care to mrs.N with hypertension through a nursing process approach. The research method was conducted in the form of a case study on mrs.N in the internal room of padang pariaman regional hospital on February 26 – march 2, 2026. Data collection was carried out through interviews, observations, physical examinations, and documentation. Four diagnoses were found in clients with a diagnosis of hypertension, namely the risk of ineffective cerebral perfusion, acute pain, sleep pattern distubances, and activity intolerance. The nursing evaluation showed that blood pressure was 132/82 mmhg, pulse 88x/minute, pain decreased to scale 1, and sleep pattern disturbances and activity intolerance were resolved within 3 days. The family is expected to play an activity role in supporting patient compliance in treatment to prevent further complications and it is hoped that clients can adopt a healthy lifestyle by consuming food contsining low salt.